The Effectiveness of Basic Physics Experiment Module Based on Guided Inquiry Model in Improving Hard Skills and Soft Skills of Prospective Physics Teachers (Jurnal Pendidikan Fisika Indonesia, 2018)
The purpose of this research is to identify the effectiveness of the first basic physics practice module based on guided inquiry on improving students’ hard skills and soft skills. The experimental design is "One Group Pretest-Pottest Control Groups Design". The samples of the research are the students who take the first basic physics practice. Data analysis techniques were effect size and gain score. Based on the result of the research, it was found that the improvement of hard skills and soft skills of the students reached 0.49 and 0.61 which was categorized as moderate. For effect size obtained data of 2.65 and 3.61 for hard skills and soft skills are categorized very high. It can be concluded that the effectiveness of the use of the first basic physics practice module based on guided inquiry is very significant to improve hard skills and soft skills of the students.Tujuan penelitian ini untuk mengidentifikasi keefektifan penggunaan panduan praktikum fisika dasar 1 berbasis guided inquiry terhadap peningkatan hard skills dan soft skills mahasiswa. Desain eksperimen yang digunakan adalah One Group Pretest-Postest Control Groups Design. Sampel penelitian adalah mahasiswa yang menempuh praktikum fisika dasar 1. Teknik analisis data yang digunakan adalah effect size dan gain score. Berdasarkan hasil penelitian diperoleh peningkatan hard skills dan soft skills mahasiswa mencapai 0.49 dan 0.61 yang berkategori sedang. Hal ini menunjukkan bahwa penggunaan panduan praktikum fisika dasar 1 dapat meningkatkan hard skills dan soft skills mahasiswa. Untuk uji effect size diperoleh data sebesar 2.65 dan 3.61 untuk hard skills dan soft skills yang berkategori tinggi. Dari hasil penelitian dapat disimpulkan bahwa kefektivitas penggunaan modul panduan praktikum fisika dasar 1 berbasis guided inquiry sangat efektif untuk meningkatkan hard skills dan soft skills mahasiswa.